The Influence of Ocean Current Patterns on Surface Marine Debris Distribution In Makassar City Waters (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
A survey of the abundance and distribution of macro debris (>2.5 - 0.5 –
Keywords: Marine debris, macro debris, meso-debris, floating, pollution, Makassar